Comparative Study of Clinical Outcomes Following Suprapatellar versus Infrapatellar Approach for Intramedullary Nailing of Tibial Fractures - Dr. Rahul Bains; Dr. Abhishek, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Intramedullary nailing (IMN) remains the standard treatment for tibial shaft fractures. The infrapatellar (IP) approach is traditional but associated with anterior knee pain and malalignment. The suprapatellar (SP) approach has emerged as a potential alternative with hypothesized advantages. Aim: To compare clinical outcomes following suprapatellar versus infrapatellar IMN in patients with tibial shaft fractures. Methods: A prospective comparative study was conducted on 180 patients (SP group, n=88; IP group, n=92) over 18 months. Baseline demographics, intraoperative parameters, postoperative complications, and functional outcomes at six months were assessed using validated scores (Lysholm, Kujala). Radiological union time and complication rates were also evaluated. Statistical significance was set at p<0.05. Results: Baseline characteristics were comparable between groups (p>0.05). The SP group demonstrated significantly better functional scores (Lysholm: 89.4±6.7 vs. 82.8±8.5, p<0.001; Kujala: 88.1±7.4 vs. 79.6±9.3, p<0.001) and greater knee range of motion (130.5°±11.8 vs. 122.7°±15.2, p<0.001). Anterior knee pain incidence was significantly lower in the SP group (13.6% vs. 33.7%, p=0.001). Radiological union time was faster (18.2±4.1 weeks vs. 20.6±5.2 weeks, p<0.001), with shorter operative time and reduced blood loss observed in the SP group. No significant differences were found in infection or nonunion rates. Conclusion: The suprapatellar approach for tibial IMN offers superior functional outcomes, reduced anterior knee pain, better alignment, and operative advantages compared to the infrapatellar approach. It represents a preferable technique for tibial shaft fracture management.